1996
DOI: 10.1002/eji.1830260722
|View full text |Cite
|
Sign up to set email alerts
|

Genetically resistant mice lacking interleukin‐12 are susceptible to infection with Leishmania major and mount a polarized Th2 cell response

Abstract: Mice with homologous disruption of the gene coding for either the p35 subunit or the p40 subunit of interleukin-12 (IL-12) and derived from a strain genetically resistant to infection with Leishmania major have been used to study further the role of this cytokine in resistance to infection and the differentiation of functional CD4+ T cell subsets in vivo. Wild-type 129/Sv/Ev mice are resistant to infection with L. major showing only small lesions which resolve spontaneously within a few weeks and develop a typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
311
3
3

Year Published

1998
1998
2008
2008

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 445 publications
(325 citation statements)
references
References 37 publications
8
311
3
3
Order By: Relevance
“…Several studies have identified IL-12 as a key component in the development of the early immune response after Leishmania infection (29,44). DC have been shown to mediate the priming of Leishmania-specific T cells (49) and to produce high levels of IL-12 after exposure to parasite Ag (18,19), thus promoting the development of protective Th1 cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have identified IL-12 as a key component in the development of the early immune response after Leishmania infection (29,44). DC have been shown to mediate the priming of Leishmania-specific T cells (49) and to produce high levels of IL-12 after exposure to parasite Ag (18,19), thus promoting the development of protective Th1 cells.…”
Section: Discussionmentioning
confidence: 99%
“…The mice were purchased from Charles River Breeding Laboratories (Sulzfeld, Germany) and, during experimentation, were kept under conventional conditions in an isolation facility. IL-12p35 Ϫ/Ϫ mice were generated as described (29) and backcrossed into a BALB/c background (30).…”
Section: Micementioning
confidence: 99%
“…A reduction in IL-12 production or an increase in IL-10 secretion results in an imbalance of Th1/Th2 cytokines that impairs healing during the later stages of Leishmania infection [46,47]. To characterize the T cell response associated with L. major infection in LysMCrePten flox/flox mice, we determined the cytokine profile produced by cells in the draining LN of Pten flox/flox and LysMCrePten flox/flox mice 4 wk after infection with L. major.…”
Section: Impaired Ifn-c-induced No Synthesis Inos Expression and Tnfmentioning
confidence: 99%
“…50,51 Introduction of a null allele at the IL-12 locus on a C57Bl/6J genetic background abrogates natural resistance to infection with M. tuberculosis, 52 and Leishmania major. 53 Finally, IL-6 and its receptor (IL-6R, one subunit of which maps on Chr.3) act synergistically with a number of other growth factors and cytokines to sustain normal proliferation and maturation of macrophages, T and B cells, and megakaryocytes. 49 IL-6 also behaves as an anti-inflammatory cytokine to control local and systemic inflammatory responses.…”
Section: Genes and Immunitymentioning
confidence: 99%